Creutzfeldt-Jakob Disease: Alterations of Gut Microbiota - Guo, Yanjun; Xu, Yichen; Lin, Xue; Zhen, Zhen; Yi, Fang; Guan, Hongzhi; Shi, Qi; Sun, Wenjie; Yang, Anchao; Dong, Xiaoping; Wang, Jiawei (Frontiers in Neurology, 2022)
Introduction Human gut dysbiosis has been implicated with the onset of many neurodegenerative disorders. However, the current data focused on the gut microbiota of patients with Creutzfeldt-Jakob disease (CJD) are still lacking. In our study, we explored the gut microbiota alteration in patients with CJD. Method We performed 16S ribosomal RNA MiSeq sequencing in stool samples of patients with CJD and controls. Functional analysis of the gut microbiota between these two groups was based on Kyoto Encyclopedia of Genes and Genomes and Phylogenetic Investigation of Communities by Reconstruction of Unobserved States 2. Clinical rating scales were used to evaluate the association between cognitive impairment and gut microbiota alteration. Result We identified a significant alteration in both the structure and the richness of the CJD group. Function analysis revealed that the gut microbiota of patients with CJD enriched in immune signaling molecule interactions and xenobiotics biodegradation. MoCA and survival times were found to be associated with gut microbiota in patients with CJD. Conclusion We demonstrated an altered gut microbiota in patients with CJD, which was associated with the cognitive impairment and the survival time of these patients.